1998
DOI: 10.1074/jbc.273.4.2136
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent Protein Kinase Interacts with Antigen Receptor Response Element Binding Proteins NF90 and NF45

Abstract: The DNA-dependent protein kinase (DNA-PK) is composed of a large catalytic subunit of approximately 470 kDa (DNA-PKcs) and the DNA-binding protein, Ku. Absence of DNA-PK activity confers sensitivity to x-rays and defects in both DNA double-strand break repair and V(D)J recombination. However, the precise function of DNA-PK in DNA double-strand break repair is not known. Here we show, using electrophoretic mobility shift assays, that polypeptides in a fraction purified from human cells interact with DNA-PK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 42 publications
5
101
1
Order By: Relevance
“…The isolated C-terminal region of NF90, containing the two dsRBMs, is much more efficiently phosphorylated than the full-length protein, suggesting that the N-terminal region of NF90 impedes its phosphorylation by PKR. The N terminus of NF90, when added to a kinase assay alone, does not inhibit PKR function, 3 consistent with a conformational change in NF90 allowing PKR increased access to the protein. As diagrammed in Fig.…”
Section: Fig 7 Nf90 Modulates Pkr Autophosphorylation Activitymentioning
confidence: 83%
See 1 more Smart Citation
“…The isolated C-terminal region of NF90, containing the two dsRBMs, is much more efficiently phosphorylated than the full-length protein, suggesting that the N-terminal region of NF90 impedes its phosphorylation by PKR. The N terminus of NF90, when added to a kinase assay alone, does not inhibit PKR function, 3 consistent with a conformational change in NF90 allowing PKR increased access to the protein. As diagrammed in Fig.…”
Section: Fig 7 Nf90 Modulates Pkr Autophosphorylation Activitymentioning
confidence: 83%
“…Additionally, NF90 and NF45 were co-immunoprecipitated with antibodies directed against PKR (lanes 2 and 7). Since NF45 does not directly interact with PKR in vitro, 3 we conclude that PKR is found in complexes with NF90 and NF45 in both cytosolic and nuclear extracts.…”
Section: Nf90-pkr Interactionsmentioning
confidence: 98%
“…Data bank analysis indicates that the NFARs may be targeted by a number of kinases in the cell, since consensus phosphorylation sites for both protein kinase C and casein kinase II are evident. Finally, a recent report also indicates that the partial NFAR clone NF-90 may also be a substrate for DNA-PK (70).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Ku interacts with DNA substrates to form protein⅐DNA complexes in electrophoresis mobility shift assays. However, DNA-PKcs does not interact with DNA in this assay, and the interaction among DNA-PKcs, Ku, and DNA is weak in the absence of cross-linkers (30). Here, we used 0.1% glutaraldehyde to stabilize the complex.…”
Section: Ku Mediates the Interaction Between Wrn And Dna-pkcsmentioning
confidence: 99%